(untitled) - Meriam, J. L. (New York, 1998)
Volume 2, Dynamics, contains 114 sample problems and 1482 unsolved problems from which a wide choice of assignments can be made. Of these problems, approximately 50 percent are new to the fourth Edition. SI units are used throughout the book.
Keywords: Mechanics, applied